Pwede! a universal model for community empowerment - Franco, Tami T.; Del Castillo, Nicolo (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
PWDs or Persons with Disabilities have long been under-accommodated due to the lack of accessibility in the urban environment. The lack of awareness and acceptance of the conditions experienced by the PWD populace reduces their social status as secondary citizens. This thesis aims to address the issues that is related to the betterment of Persons with Disabilities in the modern Philippine context while providing insights and architectural considerations as a new standard of universal design. The approach is done through discussion of the social, economical and logistical issues and solutions that are present in the research period, analysis of local and foreign precedents, and studies of the possible results. It lead to the conceptualization of an integrative environment, the universal community center, that juxtaposes the balance of aesthetic and function to generate awareness to the issues at hold. The expected resulting effect of the normalization of this environment blurs the distinction between disabilities which helps transcend the current conditions of the people with disabilities along with the community.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Persons with Disabilities environment; Persons with Disabilities Center -- Architectural Design